Generation W: From the Young People’s Perspective - Isidora Jarić (University of Belgrade, 2016)
This paper discusses the position of young people in Serbia after October 5th 2000, as can be inferred from the evidence collected in the study ‘Politics and everyday life: Serbia 1999-2002’. The author identifies amongst young people four basic modes of selfpositioning within the current social context, as described by the following labels: ‘B92 generation’, ‘provincials’, ‘fundamentalists’ and ‘guests’. These views encompass politics, their own social and political engagement, views of the future, and their own selves.